Achieving the rare : Robert F. Christy's journey in physics and beyond - Christy, I.-Juliana (World Scientific, 2013)
Robert F. Christy was a fascinating physicist who was one of the key players in some of the most dramatic events of the 20th century. He was one of Oppenheimer's students, whom Oppenheimer hailed as "one of the best in the world". He was a co-creator of the world's first nuclear reactor and the first atom bombs, of which the most practical design was called the "Christy Gadget". Later, he became a leader in the effort to contain nuclear proliferation, leading up to the SALT talks, and headed a study on long-term health effects of radiation crucial for medical safety standards. He also made pioneering contributions in the field of astrophysics, working on the variable stars (Cepheids) that are key distance indicators in the universe. Robert was equally fascinating as a person. He remarried at nearly 60 to an astrophysicist 26 years younger from some 6,000 miles initial separation. They had two daughters late in his life. Robert stayed active both professionally and physically into his nineties. He would still gallop on his horse at the age of 93. This biography is brought alive not only with words, but also with the many treasured photographs of Robert, his family, and his colleagues